2011
DOI: 10.1007/s00405-011-1846-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumors and tumor-like lesions of the eustachian tube: a systematic review of an emerging entity

Abstract: Eustachian tube (ET) primary tumors and tumor-like lesions are rare diseases presenting with common ear, nose and throat symptoms. Pathology can range from developmental anomalies to high malignant neoplasms. Hence this review aimed at suggesting a classification and outline relevant aspects of ET primary tumors and tumor-like lesions, describing clinical findings, diagnostic management and therapeutic approaches. MEDLINE, CINAHL, OVIDSP, HIGHWIRE, and GOOGLE databases were searched from inception to July 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Although specific literature on ET imaging is lacking, it is well known that CT is the most reliable imaging tool for the evaluation of middle ear, temporal bone, and bony portion of ET [1]. Magnetic resonance imaging (MRI) is superior to CT for displaying soft tissues and for differentiating tumors form normal tissues [1]. In the present case, CT image showed asymmetric mucosal thickening and enhancement of the left Rosenmuller's fossa.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Although specific literature on ET imaging is lacking, it is well known that CT is the most reliable imaging tool for the evaluation of middle ear, temporal bone, and bony portion of ET [1]. Magnetic resonance imaging (MRI) is superior to CT for displaying soft tissues and for differentiating tumors form normal tissues [1]. In the present case, CT image showed asymmetric mucosal thickening and enhancement of the left Rosenmuller's fossa.…”
Section: Discussionmentioning
confidence: 89%
“…However, the diagnosis of ET tuberculosis cannot be made solely on the basis of a nasopharyngeal examination. Although specific literature on ET imaging is lacking, it is well known that CT is the most reliable imaging tool for the evaluation of middle ear, temporal bone, and bony portion of ET [1]. Magnetic resonance imaging (MRI) is superior to CT for displaying soft tissues and for differentiating tumors form normal tissues [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumors and tumor-like lesions of the Eustachian tube (ET) are rare, and Muzzi et al 1 have reviewed 78 cases that were reported between 1988 and 2011. The pathology of ET tumors varies, and more than five reports each have described for teratoma, 2 dermoid tumors, 3 melanin-pigmented oncocytic metaplasia, 4 and chondroma 5 as benign tumors and also melanoma, 6 squamous and/or transitional cell carcinoma 7,8 as malignant tumors.…”
Section: Introductionmentioning
confidence: 99%